Assessment Of Crude Oil Degradation And Hydrocarbon Utilizing Bacteria Associated With Some Beach Soils In Ghana - Andoh-Payin, K. (University of Ghana, 2017)
Ghana discovered oil in 2007 at Cape Three Point in the Western Region. It experienced its first low-based mud oil spillage in 2009 and 2010. Ghana is therefore exposed to possible oil spillage due to oil production in commercial quantities. It is against this background that the present study is aimed to assess the degradation along the coast and identify hydrocarbon utilizing bacteria (HUB) associated with some beach soils. The beach soils were taken from eight coastal towns; Aflao, Anloga, Ada, Accra, Winneba, Cape Coast, Takoradi and Axim. The soils were contaminated with crude oil at 10 g oil /kg soil and incubated under room temperature for a period of 60 days. The contaminated soils were sampled at ten (10) days interval for HUB population and quantity of crude oil degraded. The results showed a cumulative significantly (p < 0.05) increase in the amount of crude oil degraded with time in all the soils. There was variation in degradation potential along the coast. Ada showed significantly (p < 0.05) highest degradation potential followed by Anloga. However, Takoradi and Axim soils showed the least degradation potential but was significantly (p < 0.05) lower than the others. The hydrocarbon utilizing bacteria genera associated with the soils are Bacillus, Pseudomonas, Staphylococcus and Yersinia. The dominant HUB identified was Bacillus. Further research work should be conducted to determine the diversity of HUB and enhancement of oil degradation along the coast.
Thesis (MPhil)
Keywords: Assessment; Crude Oil Degradation; Hydrocarbon; Bacteria; Beach Soils; Ghana